The Effect of Organizational Culture on Employee Performance Through the Work Motivation at Head Office of PT. Permodalan Nasional Madani - Ronald R Manurung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of organizational culture on employee performance through the work motivation of PT. Permodalan Nasional Madani. This study uses a quantitative approach with Structural Equation Modeling (SEM) using the PLS program. and IBM Statistics SPSS 26.0.. All personnel of PT. Permodalan Nasional Madani's head office are the analysis's unit of analysis. 180 people responded for the sample. A questionnaire that was sent online was used as the data gathering method. The findings demonstrated that at the PT. Permodalan Nasional Madani Head Office, work motivation can greatly moderate the impact of organizational culture on employee performance. It is stated that businesses might enhance job motivation, develop a positive company culture, andmployee performance